2011
DOI: 10.3892/or.2011.1435
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering RNA-directed targeting of RON alters invasive and oncogenic phenotypes of human hepatocellular carcinoma cells

Abstract: Abstract. The recepteur d'origine nantais (RON) receptor tyrosine kinase is highly expressed in various cancers including human hepatocellular carcinoma (HCC) and involved in tumor progression. The aims of the current study were to evaluate whether RON affects tumor cell behavior and oncogenic signaling cascades in HCC cells. We investigated the biologic role of RON on tumor cell behavior and oncogenic signaling cascades including Akt, c-Raf and extracellular signal-regulated kinase (ERK) by using the small in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In our animal models we discovered that a novel RTK, not previously linked to decorin bioactivity, is MSPR, also called RON, the receptor for the hepatocyte growth factor-like protein. This is interesting insofar as RON has been implicated in the development and progression of human HCCs (Chen et al, 1997; Cho et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…In our animal models we discovered that a novel RTK, not previously linked to decorin bioactivity, is MSPR, also called RON, the receptor for the hepatocyte growth factor-like protein. This is interesting insofar as RON has been implicated in the development and progression of human HCCs (Chen et al, 1997; Cho et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…In an HCC cell line study, RON was shown to be associated with oncogenic and invasive phenotypes ( e.g. , resistance to apoptosis, tumor cell migration, and tumor cell invasion) via AKT, c-Raf, and extracellular regulated kinase (ERK) signaling cascade modulation[ 66 ]. Clinically, RON and MET expression in patients with HCC after curative resection suggested no association of RON with overall survival and overall recurrence rates.…”
Section: Ron Receptor and Hepatobiliary Cancersmentioning
confidence: 99%
“…A study showed that small ubiquitin-like modifier (SUMO) specific protease 1 silencing resulted in a downregulation of HGF-induced proliferation and migration of HCC cells through effects on the HGF/c-Met pathway [ 109 ]. Additionally, in order to inhibit the proliferation of HCC cell lines (HepG2 and Huh7), siRNA targeting a tyrosine kinase receptor known as macrophage-stimulating protein receptor was shown to efficiently suppress tumor cell migration and invasion and enhance apoptosis by activating cleaved caspase-3 and poly (ADP-ribose) polymerase through the modulation of the Akt, c-Raf and ERK signaling pathway [ 110 ]. A study in 2019 by Zhang and colleagues evaluated the expression of sirtuin 6 (SIRT6) in a variety of HCC cell lines and its effect on the Erk1/2 signaling pathway favoring proliferation and inhibiting apoptosis.…”
Section: Tackling the Crosstalk Between The Tumor And Its Microenvmentioning
confidence: 99%